Discover new perspectives and gain insights with IDNLearn.com's diverse answers. Ask your questions and receive prompt, detailed answers from our experienced and knowledgeable community members.

What are the zeros of the quadratic function [tex]$f(x)=6x^2 + 12x - 7$[/tex]?

A. [tex]$x=-1-\sqrt{\frac{13}{6}}$[/tex] and [tex][tex]$x=-1+\sqrt{\frac{13}{6}}$[/tex][/tex]

B. [tex]$x=-1-\frac{2}{\sqrt{3}}$[/tex] and [tex]$x=-1+\frac{2}{\sqrt{3}}$[/tex]

C. [tex][tex]$x=-1-\sqrt{\frac{7}{6}}$[/tex][/tex] and [tex]$x=-1+\sqrt{\frac{7}{6}}$[/tex]

D. [tex]$x=-1-\frac{1}{\sqrt{6}}$[/tex] and [tex][tex]$x=-1+\frac{1}{\sqrt{6}}$[/tex][/tex]


Sagot :

To determine the zeros of the quadratic function [tex]\( f(x) = 6x^2 + 12x - 7 \)[/tex], we need to solve the equation [tex]\( 6x^2 + 12x - 7 = 0 \)[/tex]. The general form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a = 6 \)[/tex], [tex]\( b = 12 \)[/tex], and [tex]\( c = -7 \)[/tex] in this case.

The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

Step-by-step:

1. Identify the coefficients:
[tex]\[ a = 6, \quad b = 12, \quad c = -7 \][/tex]

2. Calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Plugging in the values:
[tex]\[ \Delta = 12^2 - 4 \cdot 6 \cdot (-7) \][/tex]
[tex]\[ \Delta = 144 + 168 \][/tex]
[tex]\[ \Delta = 312 \][/tex]

3. Apply the quadratic formula:
[tex]\[ x = \frac{-12 \pm \sqrt{312}}{12} \][/tex]

4. Simplify the expression inside the square root:
[tex]\[ \sqrt{312} = 2 \times \sqrt{78} = 2 \times \sqrt{6 \times 13} = 2 \sqrt{78} \][/tex]

5. Substitute [tex]\(\sqrt{312}\)[/tex] back into the quadratic formula:
[tex]\[ x = \frac{-12 \pm 2\sqrt{78}}{12} \][/tex]

6. Simplify the fraction:
[tex]\[ x = \frac{-12}{12} \pm \frac{2\sqrt{78}}{12} \][/tex]
[tex]\[ x = -1 \pm \frac{\sqrt{78}}{6} \][/tex]

Since [tex]\(\sqrt{78}\)[/tex] simplifies to [tex]\( \sqrt{6 \times 13}\)[/tex]:

[tex]\[ x = -1 \pm \sqrt{\frac{78}{36}} = -1 \pm \sqrt{\frac{13}{6}} \][/tex]

So, the zeros of the quadratic function are:
[tex]\[ x = -1 - \sqrt{\frac{13}{6}} \quad \text{and} \quad x = -1 + \sqrt{\frac{13}{6}} \][/tex]

This matches the first option provided. Thus, the correct answer is:
[tex]\[ \boxed{x = -1 - \sqrt{\frac{13}{6}} \quad \text{and} \quad x = -1 + \sqrt{\frac{13}{6}}} \][/tex]